2020
DOI: 10.1088/1367-2630/ab9f6b
|View full text |Cite
|
Sign up to set email alerts
|

The interplay between local and non-local master equations: exact and approximated dynamics

Abstract: Master equations are a useful tool to describe the evolution of open quantum systems. In order to characterize the mathematical features and the physical origin of the dynamics, it is often useful to consider different kinds of master equations for the same system. Here, we derive an exact connection between the time-local and the integro-differential descriptions, focusing on the class of commutative dynamics. The use of the damping-basis formalism allows us to devise a general procedure to go from one master… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 62 publications
0
31
0
Order By: Relevance
“…A powerful connection between the local and non-local generators can be obtained with the damping-basis representation [ 38 ], when one restricts to (diagonalisable) commutative dynamics, i.e., satisfying with being the commutator [ 39 , 40 ]. In [ 41 ] it was shown, that in this case the local and non-local generators can be written as where and are functions of time (the eigenvalues of the corresponding damping-basis decompositions) and are related by where denotes the Laplace transform of the function , while denotes the inverse Laplace transform. What is more, the maps in Equation ( 10 ) can be written with bi-orthogonal bases and of operators acting on the open-system Hilbert space (the damping bases of the generators), as and, because of the commutativity of the dynamics, they are time-independent.…”
Section: Local and Non-local Representations Of Open Quantum Systementioning
confidence: 99%
See 4 more Smart Citations
“…A powerful connection between the local and non-local generators can be obtained with the damping-basis representation [ 38 ], when one restricts to (diagonalisable) commutative dynamics, i.e., satisfying with being the commutator [ 39 , 40 ]. In [ 41 ] it was shown, that in this case the local and non-local generators can be written as where and are functions of time (the eigenvalues of the corresponding damping-basis decompositions) and are related by where denotes the Laplace transform of the function , while denotes the inverse Laplace transform. What is more, the maps in Equation ( 10 ) can be written with bi-orthogonal bases and of operators acting on the open-system Hilbert space (the damping bases of the generators), as and, because of the commutativity of the dynamics, they are time-independent.…”
Section: Local and Non-local Representations Of Open Quantum Systementioning
confidence: 99%
“…Though the inverse Laplace transform in Equation ( 11 ) in general cannot be calculated, the above link between the two characterisations is not only a formal one. In [ 41 ] it was shown that it enables to understand the relations between the Lindblad operator form of the two generators, as well as the connection between the (non-)Markovianity of the original and the Redfield-like approximated dynamics.…”
Section: Local and Non-local Representations Of Open Quantum Systementioning
confidence: 99%
See 3 more Smart Citations